Heteronuclear NMR spectroscopic investigations of hydrogen bonding in 2‐(benzo[d]thiazole‐2′‐yl)‐N‐alkylanilines. (9th April 2015) - Venkatachalam, T. K.; Pierens, G. K.; Bernhardt, P. V.; Reutens, D. C.
<x xml:space="preserve">Abstract</x> The 2‐(benzo[d]thiazole‐2′‐yl)‐N‐alkylanilines have previously revealed the presence of a strong intramolecular hydrogen bond. This in turn gives rise to a more complicated multiplet for the protons attached to the carbon adjacent to the amino group. This intramolecular hydrogen bond was investigated by a deuterium exchange experiment using heteronuclear NMR spectroscopy (1H, 13C, 15 N and 2H). We observed changes in the multiplet structure and chemical shifts providing further evidence that the deuterium replaces the hydrogen in the intramolecular hydrogen bond. A time course study of the D2O exchange confirmed the presence of a strong hydrogen bond. The comparison of the structures obtained by X‐ray crystallography showed a very small difference in planarity between the two‐substituted and four‐substituted amino compounds. In both the cases, the phenyl ring is not absolutely coplanar with the thiazole unit. The existence of this intramolecular hydrogen bond in 2‐(benzo[d]thiazole‐2′‐yl)‐N‐alkylanilines was further confirmed by single crystal X‐ray crystallography. Copyright © 2015 John Wiley & Sons, Ltd.